2009
DOI: 10.1007/s10439-009-9652-y
|View full text |Cite
|
Sign up to set email alerts
|

The Transport Profile of Cytokines in Epidermal Equivalents Subjected to Mechanical Loading

Abstract: Abstract-Pressure ulcer risk assessment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
1
23
2
2
Order By: Relevance
“…These trends were not consistently observed in other cytokines for a subset of the participants (Table 2), with varied participant-specific responses between strap conditions for individual cytokines (Figure 3). Previous studies have used sebum sampled with Sebutape to measure the inflammatory response during mechanical loading of the forearm using indenters 24. One such study revealed that a pressure of 100 mmHg applied for 2 hours at the volar aspect of the forearm revealed a 2.5-fold increase in IL-1α concentrations compared to the value at an adjacent unloaded control site.…”
Section: Discussionmentioning
confidence: 99%
“…These trends were not consistently observed in other cytokines for a subset of the participants (Table 2), with varied participant-specific responses between strap conditions for individual cytokines (Figure 3). Previous studies have used sebum sampled with Sebutape to measure the inflammatory response during mechanical loading of the forearm using indenters 24. One such study revealed that a pressure of 100 mmHg applied for 2 hours at the volar aspect of the forearm revealed a 2.5-fold increase in IL-1α concentrations compared to the value at an adjacent unloaded control site.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação ao processo inflamatório, estudos prévios demonstraram que fibroblastos e queratinócitos produzem citocinas pro-inflamatórias, como interleucina 1 e 6 (IL-1 e IL-6) quando em contato com peróxido de hidrogênio 18,19 . O achado de que a expressão de ambas as citocinas é elevada em resposta à exposição a agentes clareadores sugere que esses agentes são capazes de induzir uma resposta associada à cascata inflamatória 20 .…”
Section: Discussionunclassified
“…Com base nos dados obtidos no presente trabalho, conclui-se que com o aumento do período de contato do agente clareador, é observado o aumento na resposta inflamatória. Sugere-se que tal evento ocorra pela produção de citocinas pro-inflamatórias semelhantes às descritas por Terunuma et al (2001) e por Cornelissen et al (2009) 18,19 .…”
Section: Discussionunclassified
“…Pressure ulcers develop from applied pressure, resulting in periods of ischemia and damage to the epidermis 6 and through to deeper layers of tissue. This is exacerbated by cycles of ischemia-reperfusion with formation of cytotoxic free radicals, but damage occurs after a single cycle with only 2 h of ischemia.…”
Section: See the Related Editorial On Page 1708mentioning
confidence: 99%